What if? 2 eaudiobook Additional serious scientific answers to absurd hypothetical questions. - Munroe, Randall (Penguin Audio, 2022)
The #1 New York Times bestselling author of What If? and How To answers more of the weirdest questions you never thought to ask   The millions of people around the world who read and loved What If? still have questions, and those questions are getting stranger. Thank goodness xkcd creator Randall Munroe is here to help. Planning to ride a fire pole from the Moon back to Earth? The hardest part is sticking the landing. Hoping to cool the atmosphere by opening everyone’s freezer door at the same time? Maybe it’s time for a brief introduction to thermodynamics. Want to know what would happen if you rode a helicopter blade, built a billion-story building, made a lava lamp out of lava, or jumped on a geyser as it erupted? Okay, if you insist. Before you go on a cosmic road trip, feed the residents of New York City to a T. rex, or fill every church with bananas, be sure to consult this practical guide for impractical ideas. Unfazed by absurdity, Munroe consults the latest research on everything from swing-set physics to airliner catapult–design to answer his readers’ questions, clearly and concisely. As he consistently demonstrates, you can learn a lot from examining how the world might work in very specific extreme circumstances.